Rancang Bangun Sistem Monitoring dan Controlling Penerangan Jalan Umum Berbasis IoT dan Android - Rijalul Imam; I Gede Putu Wirarama Wedashwara W; Fitri Bimantoro (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
Abstract: Public street lighting (PSL) is an element or component that must be present in every road, functioning as street lighting at night for the safety of motorists. Most of public street lighting is lit at night through morning continuously without a system of monitoring and control, which is consuming electricity. Therefore in this study a prototype system was designed to monitor and control public street lighting based on IoT and Android. It use Dimmer as a microcontroller, Dimmer as a voltage regulation, and LDR sensor for taking light intensity. Conventionally, public street lighting only turns on at night and turn off during the day. Research on monitoring and controlling street lighting in addition to being made that can be ON and OFF lights, it also can reduced electric voltage to dim the light intensity. Keywords: Internet of Things, Public Street Lighting (LPJU) Relay, Dimmer, SensorLDR.